Obstacles Experienced By Students In Completing The Thesis Students - Junaidi (Universitas Serambi Mekkah, 2022)
This study aims to and out what obstacles hinder students from the Faculty ofTeacher Training and Education at Serambi Mekkah University in preparingtheir thesis. The population of this study was students of the Faculty of TeacherTraining and Education Serambi Mekkah University, Indonesian LanguageEducation Study Program, and Physical Education Study Program in preparingtheses. This type of research is qualitative research using a descriptive approach.The method used is descriptive qualitative. The total population or researchsample is 31 students. Data collection techniques through the distribution ofquestionnaires and direct interviews with the students concerned. Processing ofdata using a simple statistical formula, which uses the concept of average andpercentage. To classify the research results using the assessment norm, namelythe benchmark table of qualitative and quantitative percentages. Data processingis done manually and then presented in tabular form and discussed in narrativeform. The results of the study show some information that final year students ofthe Faculty of Teacher Training and Education Serambi Mekkah Universityexperience obstacles in the preparation of a thesis and the most dominantobstacle are the obstacle caused by the lack of facilities and infrastructure thatsupport the completion of the thesis.